Complex MLL rearrangement in non‐infiltrated bone marrow in an infant with stage II precursor B‐lymphoblastic lymphoma. (28th April 2014) - Ahlmann, Martina; Meyer, Claus; Marschalek, Rolf; Burkhardt, Birgit; Koehler, Gabriele; Klapper, Wolfram; Juergens, Heribert; Rossig, Claudia
Abstract Purpose Precursor B‐lymphoblastic lymphoma cells are indistinguishable by morphology, and immune phenotype from lymphoblasts in acute leukemia which in infancy is associated with MLL rearrangements and a poor prognosis. The role of MLL gene deregulation in rare cases of isolated lymphoblastic lymphoma in infants is obscure. We report the case of a 10‐month‐old child who presented with a cutaneous nodule on the left foot. Histological diagnosis was precursor B‐lymphoblastic lymphoma. The young age of the patient motivated us to investigate the presence of an MLL rearrangement. Methods Cytogenetic analysis was performed by fluorescence in situ hybridization (FISH), and the genomic fusion partner of MLL was identified by long‐distance inverse (LDI‐)PCR and confirmed by direct PCR. Results Fluorescence in situ hybridization screening of paraffin‐embedded formalin‐fixed tissue indeed revealed the presence of an MLL rearrangement. The genomic fusion partner was identified as AF10 by DNA sequencing of the MLL breakpoint region. The MLL‐AF10 fusion gene was further detected in cytologically normal pretreated bone marrow. Treatment was started with standard four‐drug induction chemotherapy. Because of the unfavorable outcome associated with MLL rearrangements in infant leukemia, we intensified postremission treatment according to the Interfant‐06 study protocol. The child is in continuous first remission 36 months after diagnosis. Conclusion This is the first report of submicroscopic bone marrow involvement in MLL‐rearranged isolated cutaneous B‐cell precursor lymphoma in an infant. To prospectively address the role of MLL rearrangements in extramedullary B‐lymphoblastic malignancies in infants, we suggest to assess both tumors and non‐infiltrated bone marrow for the presence of this genetic abnormality.